Formation of βTC3 and MIN6 Pseudoislets Changes the Expression Pattern of Gpr40, Gpr55, and Gpr119 Receptors and Improves Lysophosphatidylcholines-Potentiated Glucose-Stimulated Insulin Secretion - Drzazga, Anna (Cells, 2020)
The impaired spatial arrangement and connections between cells creating islets of Langerhans as well as altered expression of G protein-coupled receptors (GPCRs) often lead to dysfunction of insulin-secreting pancreatic β cells and can significantly contribute to the development of diabetes. Differences in glucose-stimulated insulin secretion (GSIS) are noticeable not only in diabetic individuals but also in model pancreatic β cells, e.g., βTC3 and MIN6 β cell lines with impaired and normal insulin secretion, respectively. Now, we compare the ability of GPCR agonists (lysophosphatidylcholines bearing fatty acid chains of different lengths) to potentiate GSIS in βTC3 and MIN6 β cell models, cultured as adherent monolayers and in a form of pseudoislets (PIs) with pancreatic MS1 endothelial cells. Our aim was also to investigate differences in expression of the GPCRs responsive to LPCs in these experimental systems. Aggregation of β cells into islet-like structures greatly enhanced the expression of Gpr40, Gpr55, and Gpr119 receptors. In contrast, the co-culture of βTC3 cells with endothelial cells converted the GPCR expression pattern closer to the pattern observed in MIN6 cells. Additionally, the efficiencies of various LPC species in βTC3-MS1 PIs also shifted toward the MIN6 cell model.